Direct measurements of Ab and Ac using vertex and kaon charge tags at the SLAC detector. - Abe, K; Abe, K; Abe, T; Adam, I; Akimoto, H; Aston, D; Baird, K; Baltay, C; Band, H; Barklow, T; Bauer, J; Bellodi, G; et al. (2005)
Exploiting the manipulation of the SLAC Linear Collider electron-beam polarization, we present precise direct measurements of the parity-violation parameters A(c) and A(b) in the Z-boson-c-quark and Z-boson-b-quark coupling. Quark-antiquark discrimination is accomplished via a unique algorithm that takes advantage of the precise SLAC Large Detector charge coupled device vertex detector, employing the net charge of displaced vertices as well as the charge of kaons that emanate from those vertices. From the 1996-1998 sample of 400 000 Z decays, produced with an average beam polarization of 73.4%, we find A(c)=0.673+/-0.029(stat)+/-0.023(syst) and A(b)=0.919+/-0.018(stat)+/-0.017(syst).